Representaciones sociales y barreras en la educación inclusiva: perspectivas de docentes de educación básica (Investigaciones) - Rendón Maca, María Mercedes (2025)
This article presents a qualitative study of the social representations of elementary and secondary school teachers at a rural school in the district of Palmaseca, Palmira-Valle del Cauca, Colombia. The objective was to analyze teacher perceptions and their relationship to learning barriers related to inclusive education. Through semi-structured interviews, their perceptions, experiences, and needs in the implementation of inclusive practices were analyzed. The results show that a lack of specific training, limited institutional support, and limited resources are determining factors in teachers’ perceptions of inclusion. It was also identified that interaction with families is key to strengthening inclusive education. It is concluded that there is a need for teacher training and institutional support to promote inclusive educational practices. Regarding intrinsic beliefs and values, they are evidently a significant influence on the adoption and implementation of teaching strategies in the classroom.